Peningkatan Pelayanan Administrasi Sekretariat Dewan (SETWAN) dalam Mendukung Fungsi DPRD Kabupaten Pandeglang: Penelitian - Ananda Algin Fadillah; Ita Rosita Wahyiah; Suherman Arifin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze and describe the improvement of administrative services by the Regional House of Representatives Secretariat (Setwan) in supporting the legislative functions of the DPRD of Pandeglang Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and document analysis. The research focused on three key aspects: human resource competence, internal coordination effectiveness, and the use of information technology, based on the framework by Wibowo (2020). The findings indicate that Setwan's administrative services are still suboptimal. Major obstacles include limited HR quality, poor interdepartmental communication, and low utilization of digital systems. Nonetheless, improvement efforts such as staff training, provision of supporting facilities, and the planning of technology-based service systems have been implemented. The study recommends strengthening institutional capacity and promoting a professional work culture within the Secretariat to enhance the effectiveness of legislative, budgeting, and oversight functions of the DPRD. These findings are expected to serve as a reference for developing more responsive, efficient, and accountable public service delivery at the regional legislative level.